Peningkatan Pemahaman Tentang Kerukunan Umat Beragama melalui Penyuluhan di Desa Mojopuro, Wonogiri - Fazrianti, Hanisa; Auliya, Fanny Nida; Farizi, Salman Al; Solihin, Muhtar Mochamad (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service aims to raise public awareness regarding religious harmony in Mojopuro Village, Wonogiri. The importance of this theme lies in strengthening the spirit of tolerance and mutual respect among different religions, races, and groups. This outreach is expected to serve as a means for the community to enhance their understanding of tolerance as a foundation for social harmony and as a platform for discussions on religious harmony. The method used in this activity is a participatory-educative approach, where participants are actively involved in listening to presentations, engaging in discussions, and asking questions. The activity is carried out through interactive material delivery, case studies, and discussion sessions involving the participants. This activity has significantly improved participants' knowledge or understanding, as observed from the results of pre-tests and post-tests conducted.